Alfalfa leaf curl virus is efficiently acquired by its aphid vector Aphis craccivora but inefficiently transmitted - Ryckebusch, Faustine; Peterschmitt, Michel; Granier, Martine; Sauvion, Nicolas (Journal of general virology, 2021)
Alfalfa leaf curl virus (ALCV) is the first geminivirus for which aphid transmission was reported. Transmission by was determined previously to be highly specific and circulative. Using various complementary techniques, the transmission journey of ALCV was monitored from its uptake from infected plant tissues up to the head of its vector. ALCV was shown to be restricted to phloem tissues using fluorescence hybridization (FISH) and electropenetrography (EPG) monitoring of virus acquisition. Furthermore, the virus is heterogeneously distributed in phloem tissues, as revealed by FISH and quantitative PCR of viral DNA acquired by EPG-monitored aphids. Despite the efficient ingestion of viral DNA, about 10 viral DNA copies per insect in a 15 h feeding period on ALCV-infected plants, the individual maximum transmission rate was 12 %. Transmission success was related to a critical viral accumulation, around 1.6×10 viral DNA copies per insect, a threshold that generally needed more than 48 h to be reached. Moreover, whereas the amount of acquired virus did not decrease over time in the whole aphid body, it declined in the haemolymph and heads. ALCV was not detected in progenies of viruliferous aphids and did not affect aphid fitness. Compared to geminiviruses transmitted by whiteflies or leafhoppers, or to luteoviruses transmitted by aphids, the transmission efficiency of ALCV by is low. This result is discussed in relation to the aphid vector of this geminivirus and the agroecological features of alfalfa, a hardy perennial host plant.